HUBUNGAN ANTARA KOHESIFITAS DAN IKLIM ORGANISASI DENGAN KINERJA KEPALA SEKOLAH SD NEGERI DI KABUPATEN SIAK - MUHAMMAD NASIR; ISJONI ISJONI; DAENG AYUB NATUNA (Universitas Riau, 2017)
The objective of this research is to analyze the relationship between cohesivenessand organizational climate with headmaster performance in Elementery School Siak Regency.The sample of the research is 80 headmaster Elementery School selected. Research conductedin the Siak Regency for approximately 3 months. The research was conducted in to March2016. The population in this study is a headmaster Elementery School in Siak Regency totaling80 headmaster and the number of samples obtained 67 headmaster. The instrument of theresearch is questioner the validity of the instrument by using product moment pearson, therealibility of the this instrument by using alpha cronbach. The results of this research are: (1)There is a positive relationship between cohesiveness (X1) with the headmaster performance(Y) with correlation ry1=0,41, (2) There is a positive relationship between organizational climate(X2) with headmaster performance (Y) with correlation ry2=0,32, and (3) There is a positiverelationship between cohesiveness (X1) and organizational climate (X2) with headmasterperformance (Y) with correlation ry12= 0,71.